Mineral Nutrient Elements in Natural Vegetation of Arid Rajasthan: I Macro Elements - Dhir, R P; Sharma, B K; Dutta, B K (Annals of Arid Zone, 2016)
Based on an analysis of 294 plant samples collected from locations spread all over arid Rajasthan, the paper presents data on the concentration in which different macro elements are present in thirty five of the commonly found species of trees, shrubs and grasses, In the trees calcium concentration ranged mostly between 2 and 3 per cent, Salvadora oleoides and Acacia senegal with much higher values were notable exceptions. Ailanthes excelsa had above average value of magnesium and phosphorus. Calcium and sodium concentrations of the shrub species were highly variable. The former element had a range from 0.85 per cent in Calligonum polygonoides to 4.57 per cent in Tamarix auriculata In comparison to trees and shrubs, grasses had low calcium content, whereas shrubs showed somewhat higher level of sodium and phosphorus than either of trees or grasses. While bringing out the interspecific differences in concentration of some of the elements, the results also show the differeences that may exist amongst the members of a given species.